The use of APE in the Problem-Based Learning Process in English subjects - Rais, Pandi; Nurdyansyah, Nurdyansyah (Universitas Muhammadiyah Sidoarjo, 2023)
Every effective, inventive, and creative educational procedure will result in high-caliber students. Hence, every instructor should be able to instruct using a good, student-friendly learning model so that when learning is implemented, pupils can do so successfully. Apart from selecting the learning model to be utilized, the teacher must have innovative ideas and methods for creating instructional materials that will be delivered to students, especially in English content, if they are to follow the learning process with ease. One of these involves employing educational media. Students will be able to follow the learning process with excitement and fun if appropriate learning materials are used, which will prevent them from becoming disinterested. With the